Challenges of Internationalization - Zavascki, Alexandre Prehn; Barth, Afonso Luís (Clinical and Biomedical Research, 2013)
The Revista HCPA has been prepared for a new challenge in the next years: its internationalization. This broad term, in the context of scientific journals, actually means that the periodic ultimately sought to be a vehicle for publishing scientific content on all fields of medical sciences including, basic, pharmacological and clinical research, from and to a worldwide readers and researchers community.